1991
DOI: 10.1577/1548-8675(1991)011<0091:htaamt>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Hoop Traps as a Means to Capture Burbot

Abstract: From 1985 through 1987, the efficacy of baited, rigid hoop traps for catching burbot Lota lota was tested in several lakes and the Tanana River in central Alaska. Experiments were conducted on the diurnal catchability of burbot, optimal baiting strategies, retention of burbot, optimal duration of soak, condition of captured burbot, size of hoop traps, recruitment to the gear, and capture‐induced behavior of burbot. Baiting was needed to capture burbot. Once caught, burbot rarely escaped the gear. Burbot held i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Hoop nets were designed to mimic those described by Bernard et al (1991) for monitoring burbot population status in Alaskan lakes (Bernard et al 1993) and rivers (Evenson 1993). Large and small hoop nets were used during 1993-1996, after 1996, small hoop nets were used exclusively because Bernard et al (1991) found no differences in size selectivity for burbot between the two net sizes.…”
Section: Methodsmentioning
confidence: 99%
“…Hoop nets were designed to mimic those described by Bernard et al (1991) for monitoring burbot population status in Alaskan lakes (Bernard et al 1993) and rivers (Evenson 1993). Large and small hoop nets were used during 1993-1996, after 1996, small hoop nets were used exclusively because Bernard et al (1991) found no differences in size selectivity for burbot between the two net sizes.…”
Section: Methodsmentioning
confidence: 99%
“…Unidentifiable fish remnants occurred in only 2.6% of stomachs containing food and came from only three individuals of the 120 lavaged. Age-0 cyprinid fishes such as blacknose dace (Rhinichthys atratulus), common (Clemens 1951;Bernard et al 1991). We captured only two burbot within this size range, which suggested that this population completes the life-history without ontogenetically switching to a fish-centered diet.…”
Section: Tl (Mm)mentioning
confidence: 90%
“…Location of study sites in northwest Connecticut, USA. hoop nets baited with previously-frozen fathead minnows (Pimephales promelas) placed in perforated plastic, screw-top containers (Bernard et al 1991).…”
Section: Study Areamentioning
confidence: 99%
“…Although no burbot spawning has been documented in tributaries recently, anecdotal data indicates that Summit and Boundary creeks were historical burbot spawning areas. Bernard et al (1991) found that burbot can be caught in 0.6 m diameter hoop nets with 25.4 mm bar web at about 350 mm TL but are not fully recruited until 450 mm TL. In an effort to predict burbot year class strength sooner than fish of 450 mm TL and evaluate recovery measures earlier, we had three hoop nets of 19 mm bar web constructed to compare to the catch to the standard web of 25.4 mm.…”
Section: Tributary Temperaturesmentioning
confidence: 99%